2018
DOI: 10.3727/096504016x14772410356982
|View full text |Cite
|
Sign up to set email alerts
|

miR-644a Inhibits Cellular Proliferation and Invasion via Suppression of CtBP1 in Gastric Cancer Cells

Abstract: Epithelial-mesenchymal transition (EMT) is one of the most important mechanisms in the metastasis of various cancers, including gastric cancer (GC). In this study, we explored the putative significance of miR-644a and its role in EMT-mediated metastasis of GC. We first detected the expression of miR-644a in a cohort of 107 GC tissues using quantitative RT-PCR. The expression of miR-644a was suppressed in GC tissues and was associated with a later clinical stage and tumor metastasis. Restoring the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…A recent report confirmed the role of miR-644a in suppressing drug resistance by inhibition of cell survival and EMT in breast cancer complementing our findings (35). Another study recently demonstrated that miR-644a inhibits gastric cancer cell proliferation and invasion as well as promotes apoptosis in liver cancer cells (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…A recent report confirmed the role of miR-644a in suppressing drug resistance by inhibition of cell survival and EMT in breast cancer complementing our findings (35). Another study recently demonstrated that miR-644a inhibits gastric cancer cell proliferation and invasion as well as promotes apoptosis in liver cancer cells (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, we used the Star-Base V3.0 database to find potential target miRNAs of BCAR4. Among the predicted target miRNAs, miR-644a is a tumor suppressor that represses multiple oncogenes [32][33][34]. In bladder cancer, BCAR4 sponges miR-644a to modulate the expression of TLX1 and promote cancer development [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we used the StarBase V3.0 database to nd potential target miRNAs of BCAR4. Among the predicted target miRNAs, miR-644a is a tumor suppressor that represses multiple oncogenes [32][33][34]. In bladder cancer, BCAR4 sponges miR-644a to modulate the expression of TLX1 and promote cancer development [9].…”
Section: Discussionmentioning
confidence: 99%